2019
DOI: 10.1101/765172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SIRT6 is a DNA Double-Strand Break Sensor

Abstract: DNA double strand breaks are the most deleterious type of DNA damage. In this work, we show that SIRT6 directly recognizes DNA damage through a tunnel-like structure, with high affinity for double strand breaks. It relocates to sites of damage independently of signalling and known sensors and activates downstream signalling cascades for double strand break repair by triggering ATM recruitment, H2AX phosphorylation and the recruitment of proteins of the Homologous Recombination and Non-Homologous End Joining pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…Tau-174Ac is translocated into the nucleus upon DNA damage SIRT6 is critical to ensure DNA repair (Mostoslavsky et al, 2006;Toiber et al, 2013). We have recently shown that it acts as a double-strand break (DSB) sensor (Onn et al, 2020) and prevents genomic instability. We have previously established a connection among DSB signaling, Tau stability and its accumulation through GSK3 activation, and Tau phosphorylation (Kaluski et al, 2017).…”
Section: Sirt6 Regulates Tau Stability and Nuclear Location Through The Deacetylation Of Residue 174mentioning
confidence: 99%
See 1 more Smart Citation
“…Tau-174Ac is translocated into the nucleus upon DNA damage SIRT6 is critical to ensure DNA repair (Mostoslavsky et al, 2006;Toiber et al, 2013). We have recently shown that it acts as a double-strand break (DSB) sensor (Onn et al, 2020) and prevents genomic instability. We have previously established a connection among DSB signaling, Tau stability and its accumulation through GSK3 activation, and Tau phosphorylation (Kaluski et al, 2017).…”
Section: Sirt6 Regulates Tau Stability and Nuclear Location Through The Deacetylation Of Residue 174mentioning
confidence: 99%
“…Our results showed that either DNA damage or SIRT6 deletion increased CBP levels in the nucleus and cytoplasm (Figures 4 and S4). SIRT6-KO cells are deficient in their ability to repair DNA, and CBP is a key player in DSB repair (Dutto et al, 2018;Mostoslavsky et al, 2006;Onn et al, 2020;Piekna-Przybylska et al, 2016;Toiber et al, 2013); thus, its overexpression might be the outcome of persistent DNA damage signaling and an important component of the cellular efforts to mitigate DNA damage. Our results show that preventing CBP activity can also ameliorate Tau accumulation and nuclear localization.…”
Section: Sirt6 Regulates Tau Stability and Nuclear Location Through The Deacetylation Of Residue 174mentioning
confidence: 99%
“…1 , bottom), including Ercc6 m/m Xpa −/− , Ercc1 −/− and Ercc1 −/d7 (mean r s = 0.24). Sirt6 −/− also showed similarity with Ercc1 −/d7 and Ercc6 m/m Xpa −/− , which may be explained by the recently discovered function of Sirt6 as a DNA strand break sensor and activator of the DNA damage response ( Onn et al, 2020 ). The only statistically significant negative correlation we found was between Tert and Sirt6 knockout mice.…”
Section: Resultsmentioning
confidence: 74%
“…The recent studies by Onn et al. 221 found SIRT6 to share a role with PARP1 as a DNA double-strand break sensor, a finding which, in conjunction with the enzyme’s function in the recruitment of proteins of the homologous recombination and non-homologous end joining pathways, may contribute to increased SIRT6 activity and efficiency of DSB repair in long-lived species. 222 To this end, SIRT6-deficient cynomolgus monkeys ( Macaca fascicularis ) displayed severe developmental retardation and dramatically reduced survival, emphasizing the protein’s role in primate development.…”
Section: Nad Functions As Substratementioning
confidence: 99%